World inequality report 2022 - Chancel, Lucas; Piketty, Thomas 1971-; Saez, Emmanuel 1972-; Zucman, Gabriel 1986- (The Belknap Press of Harvard University Press, 2022)
World Inequality Report 2022 is the most authoritative and comprehensive account of global trends in inequality, providing cutting-edge information about income and wealth inequality and also pioneering data about the history of inequality, gender inequality, environmental inequalities, and trends in international tax reform and redistribution